One piece: Vol. 79, 80, 81 - Oda, Eiichiro; Caselman, Lance; Nakatani, Andy (San Francisco, CA VIZ Media, 2009)
Join Monkey D. Luffy and his swashbuckling crew in their search for the ultimate treasure, the One Piece.
Volume 79 Lucy Volume 80 Sons' cups Volume 81 Roko
Translator and adapter may vary.
Originally published: Tokyo, Japan : SHUEISHA, Inc., 1997.
In keeping with the original Japanese format, this book reads from back to front and from right to left.
Rated T for Teen ("recommended for ages 13 and up...contains fantasy violence and tobacco usage).
Translated from Japanese.
113059
Keywords: Luffy, Monkey D; Pirates -- Comic books, strips, etc; Comic books, strips, etc. -- Japan; Swordsmen -- Comic books, strips, etc; Comics & Graphic Novels -- Manga -- Fantasy; Comics & Graphic Novels -- Manga -- Media Tie-In; Japan; Manga; Adventure story comics; Comics (Graphic works); Action and adventure comics; Graphic novels; Translations